REPRESENTATION OF INDONESIA IN WIKIPEDIA - Sunarsih (Denpasar Institute, 2020)
The objective of this study is to describe the representation of Indonesia in Wikipedia article. The approach applied in this study is corpus-based discourse analysis. This approach concerned with the key word â€œIndonesiaâ€ and how it conveyed meaning related to the other words around (collocation) in the left and right side of the word â€œIndonesiaâ€. By analyzing the collocation, the representation of Indonesia is interpreted and input as the meaning property of the word â€œIndonesiaâ€. The finding of this study shows that the word â€œIndonesiaâ€ in Wikipedia article contained meaning components such as Indonesia is a country whose rich cultural and natural resources, long history; developing technology; developing economy; facing some problem; actively participating in international affair and sport competition.